Meningkatkan Aktivitas, Berpikir Kritis Dan Komunikasi Menggunakan Model PBL, MGMTT Dan Permainan Ular Naga Di Kelas III SDN Kelayan Selatan 8 - Siti Aminah; Zain Ahmad Fauzi (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
The problem in this study is the low activity of students, the lack of critical thinking skills, and the lack of communication skills. The solution to the problem above is to use the Problem Based Learning model, MGMTT and the Dragon Snake game. This study aims to describe the activities of educators, analyze activities, critical thinking skills and communication of class III students. This study used Classroom Action Research which was carried out in 2 meetings. The subjects of this research were class III students at SDN Kelayan Selatan 8, which consisted of 14 students. The data taken is qualitative data as well as quantitative data. The indicator of research success with learning mastery is that 80% of students achieve KKM value ≥80. The results of the study showed that there was an increase in meeting I to meeting II with the acquisition of educator activities carrying out the learning model, namely obtaining "Good" criteria and increasing to "Very Good" criteria. The activity of students at meeting I "A few were active" and increased to "Almost all active" at meeting II. Students' critical thinking skills at the first meeting were "mostly critical" and increased to "almost all critical" at the second meeting. While the communication skills of the students in the first meeting were "mostly active" and increased to "almost all active" in the second meeting.